Association between serum iron levels and atherosclerotic cardiovascular diseases among American older adults: a cross-sectional study based on the National Health and Nutrition Examination Survey, 2009–2018 - Yu, Xiaochen; Li, Min; Chen, Bingxing; Qi, Yuan; Guan, Xiuru (Frontiers in Nutrition, 2024)
Background There is controversy regarding the relationship between serum iron levels and atherosclerotic cardiovascular disease (ASCVD). Objective To investigate the relationship between serum iron levels and ASCVD among older adults using data from the 2009–2018 National Health and Nutrition Examination Survey (NHANES). Methods We performed a cross-sectional analysis involving 8,682 participants aged 60 years and older, with complete data on serum iron levels and confirmed ASCVD status, sourced from the 2009–2018 National Health and Nutrition Examination Survey (NHANES). Multivariable logistic regression models were used to examine the association between serum iron levels and ASCVD. To assess the consistency of this association across different demographic groups, subgroup analyses, and interaction tests were performed. Results The group with the highest serum iron levels (fourth quartile, 100–369 μg/dL) exhibited several distinct characteristics: they were the youngest on average (69.57 ± 6.91 years), had the highest proportion of males (61.42%), and the highest hemoglobin levels (14.43 ± 1.33 g/dL). This group also showed the lowest iron supplement usage (19.71 ± 12.85 mg/30 days), white blood cell counts (6.73 ± 2.41 1,000 cells/μL), and serum creatinine levels (0.98 ± 0.45 mg/dL). Moreover, they had higher levels of education and income, a higher likelihood of being married, and a lower body mass index (BMI). Additionally, they had significantly lower rates of diabetes, hypertension, stroke, and heart attacks (all p < 0.05). After adjusting for potential confounders, a linear relationship between serum iron levels and ASCVD was initially observed (OR = 0.97; 95% CI, 0.95–0.99, p < 0.05). However, further analysis using a two-part logistic regression model with an inflection point at 131 μg/dL revealed more nuanced results. For serum iron levels below 131 μg/dL, each 10 μg/dL increase was associated with a 4% decrease in the odds of ASCVD (OR = 0.96; 95% CI, 0.93–0.98, p < 0.001). Conversely, for serum iron levels above 131 μg/dL, each 10 μg/dL increase corresponded to a 1% increase in the odds of ASCVD, though this finding was not statistically significant (OR = 1.01; 95% CI, 0.98–1.08, p > 0.05). Conclusion In the US elderly population, serum iron levels are negatively associated with ASCVD, particularly when serum iron levels are below 131 μg/dL.